Intrinsic alignment of simulated galaxies in the cosmic web: implications for weak lensing surveys. Issue 4 (11th March 2015) - Codis, S.; Gavazzi, R.; Dubois, Y.; Pichon, C.; Benabed, K.; Desjacques, V.; Pogosyan, D.; Devriendt, J.; Slyz, A.
Abstract : The intrinsic alignment of galaxy shapes (by means of their angular momentum) and their cross-correlation with the surrounding dark matter tidal field are investigated using the 160 000, z = 1.2 synthetic galaxies extracted from the high-resolution cosmological hydrodynamical simulation horizon-agn . One- and two-point statistics of the spin of the stellar component are measured as a function of mass and colour. For the low-mass galaxies, this spin is locally aligned with the tidal field 'filamentary' direction while, for the high-mass galaxies, it is perpendicular to both filaments and walls. The bluest galaxies of our synthetic catalogue are more strongly correlated with the surrounding tidal field than the reddest galaxies, and this correlation extends up to ∼10 h − 1 Mpc comoving distance. We also report a correlation of the projected ellipticities of blue, intermediate-mass galaxies on a similar scale at a level of 10 −4 which could be a concern for cosmic shear measurements. We do not report any measurable intrinsic alignments of the reddest galaxies of our sample. This work is a first step towards the use of very realistic catalogue of synthetic galaxies to evaluate the contamination of weak lensing measurement by the intrinsic galactic alignments.